Non-fungible tokens (NFTs): A review of pricing determinants, applications and opportunities - Roman Kräussl; Alessandro Tugnetti (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
This paper provides a review of the development of the non-fungible tokens (NFTs) market, with a particular focus on its pricing determinants, its current applications and future opportunities. We investigate the current state of the NFT markets and highlight the perception and expectations of investors towards these products. We summarize and compare the financial and econometric models that have been used in the literature for the pricing of non-fungible tokens with a special focus on their predictive performance. Our intention is to design a framework that can help understanding the price formation of NFTs. We further aim to shed light on the value creating determinants of NFTs in order to better understand the investors' behavior on the blockchain.
urn:nbn:de:hebis:30:3-681494
Keywords: 330